Вплив об’єму робіт на зарплату різних складів ланок при влаштуванні цем’янкової штукатурки - Терновий, В. І.; Молодід, О. С.; Молодід, О. О.; Уманець, І. М. (Ways to Improve Construction Efficiency, 2013)
The article contains research results dependencies wages plasterers at the device of 40, 100, 180 and 400 m2 opus signinum restoration plaster links, consisting of 2, 3 and 4 plasterers.